National identification and control of corruption mediated by socioemotional climate, collective efficacy, and trust in Chilean students: an experimental study - Hatibovic, Fuad Juso (2022)
This article analyzes the relationship between successful dealing with deviant acts (i.e., acts of corruption) and social cohesion. We conducted an experimental research with 148 university students based on the subjective group dynamics theory. We informed the research participants of some corruption cases in Chile (ingroup) and Argentina (outgroup) during the last year, with two modes of efficiency in their legal control: high efficiency (95% of the cases were judged and sanctioned) and low efficiency (5% of the cases were judged and sanctioned). The mediational analysis shows that the induced ingroup effectiveness causes a better emotional climate, greater perceived collective efficiency in dealing with deviance, increases confidence in social control and reinforces national identification. We conducted a comparative analysis with a sample of Portuguese university students, finding that Chilean students have a more critical view of collective effectiveness in dealing with deviance and a moderate level of national identification. The results are related to the assumptions of the subjective group dynamics theory and show the psychosocial effects of uncontrolled and unsanctioned corruption.